If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(2t + -3) + 6t = 8t + -4 Reorder the terms: -5(-3 + 2t) + 6t = 8t + -4 (-3 * -5 + 2t * -5) + 6t = 8t + -4 (15 + -10t) + 6t = 8t + -4 Combine like terms: -10t + 6t = -4t 15 + -4t = 8t + -4 Reorder the terms: 15 + -4t = -4 + 8t Solving 15 + -4t = -4 + 8t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-8t' to each side of the equation. 15 + -4t + -8t = -4 + 8t + -8t Combine like terms: -4t + -8t = -12t 15 + -12t = -4 + 8t + -8t Combine like terms: 8t + -8t = 0 15 + -12t = -4 + 0 15 + -12t = -4 Add '-15' to each side of the equation. 15 + -15 + -12t = -4 + -15 Combine like terms: 15 + -15 = 0 0 + -12t = -4 + -15 -12t = -4 + -15 Combine like terms: -4 + -15 = -19 -12t = -19 Divide each side by '-12'. t = 1.583333333 Simplifying t = 1.583333333
| 2/7x4/11 | | 3/17=x/9 | | 1/5v-5/2=-7/3 | | 15+3b=0 | | P+51=68 | | (2x-3)(5x+9)=0 | | 2=(x-54166)/10200 | | 4v^3*vu^2=4v^4u^2 | | x^2+4x-190=0 | | 13x+9c=1703 | | 9x+5+x=-9+7x+8 | | 6(x-30)=4(x+10) | | 2x+1-3x+5=2(2x+5)-x | | 7y-6v-10=13 | | 49x^2-11=0 | | 2tan^2(x)=0 | | 5x-6=7x+2(x-3) | | 6x(2t-4)=48-6t | | 2y^2*3x=6xy^2 | | x*2+x=387 | | -31/2/2 | | -x^2+100x-1600=0 | | (2ab-2ac-2bc)(ab+ac+bc)= | | (x^2-5x+3)(2x^2+x-7)=0 | | (x-7)(x-4)=0 | | 8a^3+64b^3= | | 63/40= | | 0=3x^2+18x+18 | | 2/5m=8 | | -y+5.3+(7.2y-9)=6.2y+n | | 1188=-2x^2+98x | | x^2-63=18x |